THE EFFECT OF FREE SHIPPING PROMOTION STRATEGIES AND PRODUCT AVAILABILITY ON PUBLIC PURCHASE FREQUENCY GOLAMBANUA II VILLAGE ON THE SHOPEE APPLICATION - Albert Ferikusman Fatemaluo; Aferiaman Telaumbanua; Tiarni Duha; Otanius Laia (LPPM YPITI, 2026)
This research is motivated by the increasing use of the Shopee application among the people of Golambanua II Village, which is thought to be influenced by the free shipping promotion strategy and product availability. The purpose of this study is to analyze the influence of these two factors on the frequency of purchases on Shopee. This study uses a quantitative approach with an associative method. The research sample consisted of 63 respondents selected through a purposive sampling technique with the criteria of having used the Shopee application in the last three months. Data were collected using a Likert scale questionnaire and analyzed through validity tests, reliability tests, classical assumption tests, and multiple linear regression with the help of SPSS version 27 software. The results showed that the free shipping promotion (β = 0.449; Sig. = 0.000) and product availability (β = 0.810; Sig. = 0.000) had a positive and significant effect on the frequency of purchases, both partially and simultaneously (F count = 238.512; Sig. = 0.000). The coefficient of determination (R²) of 0.888 indicates that 88.8% of the variation in purchase frequency can be explained by these two variables. The conclusion of this study confirms that free shipping promotions and product availability play a strategic role in increasing purchase frequency, with product availability being the dominant influence.